Pengembangan Edu-Game Al-Qur’an Berbasis Android Untuk Meningkatkan Hafalan Al-Qur’an pada Peserta Didik Jenjang Sekolah Dasar - Nurfadhilah, Nada; Susilo, Mohamad Joko (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The development of increasingly sophisticated educational technology is an opportunity, especially in the world of education, because it can be utilized in the learning process in the form of interactive learning media in the subjects of Islamic Religious Education and TBTQ (Complete Reading and Writing Al-Qur'an). This research aims to develop media in the form of an Android application to improve students' memorization of the Al-Qur'an at elementary school level. This research method uses a development research approach with a 4D model (define, design, develop, disseminate). Data collection techniques were carried out by observation, interviews, tests and questionnaires. Data analysis techniques use qualitative and quantitative descriptive analysis. Based on the research results, it was found that media testing by media experts obtained a score of 93.75%, material experts 100%, learning experts 97.43%. The results of the limited test at SD N Pandanpuro 2 obtained a score of 88.06%. The field test results at SD N Purworejo were 77.37%, SD N Kaliurang 1 was 79.85%, and SD N Banteng was 83.92%. From the overall test results it can be said that the application developed is in the feasible category for implementation.